PENGEMBANGAN MEDIA BRAINLY BATTLE BERBASIS KEARIFAN LOKAL PADA MATA PELAJARAN IPAS MATERI SIFAT DAN PERUBAHAN WUJUD BENDA KELAS V SEKOLAH DASAR - Hanif Daffa Praditya; Filia Prima Artharina; Sunan Baedowi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The use of suboptimal learning media has resulted in a low level of student interest and involvement in the learning process. The aim of this study was to determine the validity of local intelligence-based media called Brainly Battle when used on IPAS subjects, in relation to their material characteristics and dynamics of change. Research and Development, or R&D, provides the basis for the models used in these surveys. The only purpose of creating Brainly Battle based learning media is to analyze the effectiveness of learning media in relation to local wisdom. This research was done at SD N 3 Gedong. The evaluation was conducted using the Likert scale examination list of teachers and the Guttman scale form of students, which required a "Yes" or "No" answer. It can be concluded that local intelligence-based learning media Brainly Battle can serve as a valuable tool for student learning. All media expert validation findings are good, with a success rate of 97.3% for material validation. Overall, the creation of Brainly Battle educational media that focuses on local intelligence, IPAS material characteristics, and the evolutionary nature of subjects in the fifth grade elementary school curriculum is considered highly commendable. Field trials showed that the implementation of a responsive teaching approach in class V resulted in achievement rates of 91.6% and 95% for teachers. The conclusions were drawn from the field trials.